Naltrexone extended-release injection: an option for the management of opioid abuse - Taylor Jr R; Raffa RB; Pergolizzi Jr JV (Dove Medical Press, 2011)
Robert Taylor Jr1, Robert B Raffa2, Joseph V Pergolizzi Jr3,41NEMA Research Inc, Naples, FL, 2Department of Pharmaceutical Sciences, Temple University School of Pharmacy, Philadelphia, PA, 3Department of Medicine, Johns Hopkins University School of Medicine, Baltimore, MD, 4Department of Anesthesiology, Georgetown University School of Medicine, Washington, DC, USAAbstract: The United States Food and Drug Administration (FDA) approved naltrexone, a synthetic competitive antagonist at opioid receptors, in oral form in 1984 for use in the management of opioid abuse and addiction. Because naltrexone and its major metabolite, 6-ß-naltrexone, are both competitive antagonists at opioid receptors – and thereby inhibit opioid agonist-induced effects including those desired by abusers – it was hypothesized that once maintained on naltrexone, opioid-induced desirable effects would be diminished to the point that relapse to illicit use would decline because it was no longer rewarding. However, good medication compliance is a requisite for such a strategy to be effective and a systematic review of oral naltrexone concluded that this method of treatment was not superior for any outcomes measured (ie, retention, abstinence, or side effects) to placebo, psychotherapy, benzodiazepines, or buprenorphine treatment. In addition, the retention rate on oral naltrexone was very low (less than 30%). Recently, the FDA approved an extended-release formulation (intramuscular depot injection) of naltrexone for prevention of relapse to opioid dependence following opioid detoxification and to be used along with counseling and social support. Since it needs to be administered only monthly, as opposed to the daily administration required for the oral formulation, naltrexone injection has the potential for increasing adherence and retention rates. Concerns include liver damage at high doses (oral formulation) and possible opioid overdose if an attempt is made to surmount receptor antagonism by taking higher doses of an opioid agonist or if opioid receptors become "sensitized" under long-term antagonism. The focus of the present review is the current information regarding the safety and efficacy of naltrexone extended-release therapy.Keywords: opioid dependence, relapse prevention, depot injection, extended-release naltrexone